Epithelial–Myoepithelial Carcinoma of the Esophagus: A Case Report - Wu, Haohao; Zhang, Fangbiao; Peng, Jiahui; Wu, Zhiju; Zhang, Xiangyan; Wu, Xingzhen (Frontiers in Surgery, 2022)
Epithelial myoepithelial carcinoma (EMC) of the esophagus is a rare biphasic tumor with low malignant potential which has not previously been reported in the published literature. The present study describes the case of asymptomatic, 53-year old male who presented with epithelial-myoepithelial carcinoma in the esophagus during gastroscopic examination. Esophageal computed tomography (CT) showed thickening of the wall of the lower esophagus with a thickness of about 0.7cm, and enhanced scan showed uneven enhancement of the thickened esophageal wall. Thoracoscopic esophagectomy was performed due to the tumor was malignant. Histopathology revealed the tumor was characterized by biphasic architecture consisting of cuboidal ductal cells and myoepithelial cells. The patient's postoperative recovery was eventful, anastomotic fistula occurred, and the patient was discharged after 84 days in hospital. One year postsurgery, The patient has remained in good health, with no evidence of metastasis and recurrence.